2021
DOI: 10.1093/eurpub/ckaa229
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related and contextual aspects of suboptimal adherence to antiretroviral therapy among persons living with HIV in Western Europe

Abstract: Background The daily oral dosing requirement for antiretroviral therapy (ART) may be challenging for some people living with HIV (PLWHIV) with comorbid conditions, confidentiality concerns or pill fatigue. We investigated suboptimal adherence from the perspective of PLWHIV and HIV physicians. Methods PLWHIV on ART (n = 688) and HIV physicians (n = 120) were surveyed during 2019 in France, Germany, Italy and the UK. Suboptimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Research also links poor mental health to HIV risk by reducing the likelihood of condom use during sex, increasing utilization of substances, and elevating numbers of sexual partners [ 6 , 18 , 19 ], all well known risk factors for HIV transmission. A study in France, Germany, Italy, and the United Kingdom indicated that depression was associated with reduced adherence to HIV treatment among PLHIV [ 20 ]. A meta-analysis of 39 studies, reported significant associations between depression and lower odds of retention in HIV care among PLHIV [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research also links poor mental health to HIV risk by reducing the likelihood of condom use during sex, increasing utilization of substances, and elevating numbers of sexual partners [ 6 , 18 , 19 ], all well known risk factors for HIV transmission. A study in France, Germany, Italy, and the United Kingdom indicated that depression was associated with reduced adherence to HIV treatment among PLHIV [ 20 ]. A meta-analysis of 39 studies, reported significant associations between depression and lower odds of retention in HIV care among PLHIV [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other participants reported depression, dizziness, and headache which resulted in treatment discontinuation. Since it has been demonstrated that experiencing side effects may result in poor adherence [ 24 , 25 ], there is need for support from health care providers to encourage patients to report any unusual event from the drug, manage toxicities as well as offer adherence support.…”
Section: Discussionmentioning
confidence: 99%
“…A targeted literature review was conducted to inform the initial draft of the health states. This review focused on the experience of living with HIV [4,10,17,18,36], ART [10,12,36,37], and the ART treatment process [12,15,16,[38][39][40][41]. Based on this literature, initial drafts of four health states were developed, along with a detailed background information document providing details on the four ART options.…”
Section: Health State Developmentmentioning
confidence: 99%